(untitled) (The Research of Medical Science Review, 2024)
Chronic Kidney Disease (CKD) is a global public health issue, with emerging evidence highlighting the roles of environmental agents, particularly lead and hepcidin dysregulation, in its progression. This study investigated the association between blood lead, hepcidin, and CKD in 75 participants, including 50 CKD patients and 25 healthy controls, from Pakistan. Serum hepcidin, blood lead, serum urea, and creatinine levels were significantly elevated in CKD patients, while eGFR, serum iron, and hemoglobin levels were notably lower compared to controls. Serum hepcidin showed a positive correlation with blood lead, serum urea, and creatinine levels, and a negative correlation with eGFR, serum iron, and hemoglobin. Multivariate regression analysis identified blood lead, serum urea, and creatinine as significant positive predictors of serum hepcidin, while eGFR, serum iron, and hemoglobin were significant negative predictors (P < 0.05). The findings underscore the bidirectional relationship between hepcidin, lead exposure, and CKD progression, suggesting that elevated hepcidin correlates with renal impairment, lead burden, and anemia due to iron catabolism. Monitoring hepcidin and mitigating lead exposure may offer therapeutic strategies for managing CKD. These results emphasize the need for further research on hepcidin modulation and lead reduction to improve CKD patient outcomes.